Cu(triNHC)-catalyzed polymerization of glycidol to produce ultralow-branched polyglycerol - Sung, Kihyuk; Baek, Jinsu; Choi, Soonyoung; Kim, Byeong Su; Lee, Sang Ho; Lee, In Hwan; Jang, Hye Young (RSC Advances, 2023)
We have successfully synthesized a novel form of polyglycerol with an unprecedentedly low degree of branching (DB = 0.08-0.18), eliminating the need for glycidol protection. Leveraging the remarkable efficiency and selectivity of our Cu(triNHC) catalyst, comprising copper(i) ions and NHC ligands, we achieved a highly selective polymerization process. The proposed Cu-coordination mechanisms presented the formation of linear L1,3 units while effectively suppressing dendritic units. Consequently, our pioneering approach yielded polyglycerol with an ultralow DB and exceptional yields. To comprehensively assess the physical properties and topology of the synthesized polyglycerol, we employed 1H diffusion-ordered spectroscopy, size-exclusion chromatography, and matrix-assisted laser desorption/ionization-time of flight spectrometry. Remarkably, the ultralow-branched cyclic polyglycerol (DB = 0.08) synthesized at 0 °C showcased extraordinary characteristics, exhibiting the lowest diffusion coefficient and the highest molecular weight. This achievement establishes the significant potential of our polyglycerol with a low degree of branching, revolutionizing the field of biocompatible polymers.
Keywords: Catalyzed polymerization; Degree of branching; Glycidol; Low degree; NHC ligands; Polyglycerols; Polymerization process; Selective polymerizations; Synthesised; ]+ catalyst